Penerapan Metode Cooperative Script Dalam Meningkatkan Hasil Belajar Siswa - Ferasiska Y Hasim; Irina Popoi; Ardiansyah ardiansyah (Jambura Economic Education Journal, 2019)
Ferasiska Y Hasim Nim 911 415 116 "Application of Cooperative Script  Learning Method in Improving Learning Outcomes ". Undergraduate Economic Education Study Program, Department of Economic Education, Faculty of Economics, Gorontalo State University The research aimed to improve student’s learning outcomes at integrated social science subjek in SMP Negeri 1 Kabila of bone bolango District, Gorontalo Province. The methode applied in this research was classroom action research that was conducted in II cycles and involved  27 people. The finding of research found that result of this classroom action research in cycle I reached 62,97% then increased to 81,49% in cycle II meanwhile, students who were not completed would be remedied through the implementation of cooperative script method at integrated social Science subjek in grade VIII thus the students’ learning outcomes Improved. Keywords: Cooperative Script, Student Learning Outcomes